The nature of interphase potential under forced movement of the proton in water/oxygen system - Pershina, Katerina (My University, 2016)
The effect of oxygen bubbles on the formation of the membrane interfacial potential under microgravity in water media was considered. The braking of the proton motion and changes of pH under microgravity in water/oxygen systems depend on the O2 gas bubble size distribution, that have a much larger variance in acid solutions than in basic solution.
Keywords: membrane; proton; oxygen; interphase potential; мембрана; протон; кисень; трансграничний потенціал; кислород; трансграничный потенциал